THE IMPORTANCE OF NEW TECHNOLOGIES IN THE MILITARY EDUCATION OF OFFICERS - Vuletić, Dejan (The Policy of National Security, 2025)
The integration of technology into military education, as well as education in general, represents a reality, a need, and a necessity for efficient functioning and survival in the information society. The subject of this paper is an analysis of the importance and application of new technologies (artificial intelligence, virtual reality, augmented reality, etc.) in military education. This paper aims to highlight, first and foremost, the needs and possibilities of applying new technologies, as well as the positive effects of their implementation on officers, future leaders (including commanders, chiefs, etc.). By analyzing the content, specifically relevant scientific sources and practical examples, it becomes clear which new technologies are the most significant in military education. The application of new technologies undoubtedly results in greater efficiency in mastering the planned teaching content. It makes teaching and training safer, more interactive and more interesting, and as a result, officers are better equipped and prepared to confront modern challenges, risks and threats to security. New technologies already play a significant role and have numerous applications in military education. In particular, underdeveloped segments require implementation, investment, or adaptation processes to keep pace with the demands of the security environment. The role of new technologies will continue to be increasingly represented in the future, characterized by the use of innovative tools.
Keywords: military; education; training; officiers; new technologies